1960
DOI: 10.1192/bjp.106.445.1555
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nicotinic Acid, Nicotinamide, and Placebo on the Chronic Schizophrenic

Abstract: For various reasons we became interested in the possibility that nicotinic acid or nicotinamide might be of some benefit to the chronic schizophrenic. Many workers have noticed clinical similarities between the acute schizophrenias and the encephalopathies of nicotinic acid deficiency (4). Nicotinic acid is known to be of value in pellagra (2) and in the treatment of delirium tremens and allied states (1), and Osmond and Hoffer have had promising results with these substances in the treatment of schizophrenia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

1969
1969
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 2 publications
0
3
2
Order By: Relevance
“…Also at variance with the reported beneficial therapeutic findings (Hoffer et al, 1957;Hoff er, 1962;Osmond and Hoffer, 1962;Hoffer and Osmond, 1964), O' Reilly (1955) found no therapeutic effects with nicotinic acid in a group of chronic schizophrenic patients; Ashby et al (1960) obtained completely nega tive results with nicotinamide in chronic schizophrenics; Ramsay et al (1970) found that the addition of nicotinic acid or nicotinamide to a regular phenothiazine treatment regime over a 6-month period did not add any measurable therapeutic effect, and there were certain indications that nicotinic acid or nico tinamide may have had negative therapeutic effects; found that there was no difference in the rehospitalization rate and in major tranquilizer use between the control group and a group of patients given nicotinic acid (3,000 mg/day) or an active placebo (nicotinic acid, 6 mg/day) as adjuvant medication in accordance with a double-blind design over a 2-year period.…”
Section: Heyman and Merliscontrasting
confidence: 43%
“…Also at variance with the reported beneficial therapeutic findings (Hoffer et al, 1957;Hoff er, 1962;Osmond and Hoffer, 1962;Hoffer and Osmond, 1964), O' Reilly (1955) found no therapeutic effects with nicotinic acid in a group of chronic schizophrenic patients; Ashby et al (1960) obtained completely nega tive results with nicotinamide in chronic schizophrenics; Ramsay et al (1970) found that the addition of nicotinic acid or nicotinamide to a regular phenothiazine treatment regime over a 6-month period did not add any measurable therapeutic effect, and there were certain indications that nicotinic acid or nico tinamide may have had negative therapeutic effects; found that there was no difference in the rehospitalization rate and in major tranquilizer use between the control group and a group of patients given nicotinic acid (3,000 mg/day) or an active placebo (nicotinic acid, 6 mg/day) as adjuvant medication in accordance with a double-blind design over a 2-year period.…”
Section: Heyman and Merliscontrasting
confidence: 43%
“…Alvarez (1967); Cott (1967); Denson (1962); Herjanic et al (1967); Maslowski (1961); Newbold (1970); Robie (1971); Saarma andVasar (1970), andTobin (1967). Nevertheless, at variance with the reported beneficial therapeutic findings with nicotinic acid, Ashby et al (1960) found no therapeutic effects with nicotinamide in chronic schizophrenic patients and McGarth et al (1972) have failed to show any significant difference in therapeutic results between patients on the active (nicotinamide) and inactive (placebo) tablets 2 years after the commencement of drug administration. The same applies to O' Reilly (1955) and Vallely et al (1971) who failed to obtain therapeutic changes with nicotinic acid in schizophrenic patients.…”
Section: Findings In Clinical Trialscontrasting
confidence: 41%
“…The results of some subsequent studies have demonstrated positive effects with niacin in the treatment of schizophrenia (e.g., Denson 1962), but this finding has not been universal (e.g., Ashby, Collings, and Bassett 1960;Greenbaum 1970;Ban 1981). The most comprehensive evaluation of using niacin to treat schizophrenia was undertaken in a series of studies sponsored by the Canadian Mental Health Association (Ban 1981).…”
Section: Treatment Of Schizophreniamentioning
confidence: 93%